A experiência de planejamento e orçamento em uma autarquia federal. O caso da CVM - comissão de valores imobiliários - Castro, Antônio Roberto da Costa (2001)
The main objective of this case study is centered in reasearching the identification of the influences that exert the budgetary restrictions in the strategical planning of the CVM. Through this work we will try to identify the relation between the planning made for the institution and its operationalization. Consequent1y, the challenges that the institution faced on its path to reach its objectives and to accomplish its mission, having as a background the relation between the planning and the scarce budgetary resources. We consider that the bibliographical references used are sufficient to support the analysis and the scope ofthe study. We will analyze the plannings and the budget (proposed and authorized), in a fractionated timeframe, year after year. Such fractions shall not harm the visualization of continuity of the actions that had been implemented throught time. As important as the study mentioned above, it will be to support in detail the role of the state, promoting the development of the market through its actions, in a policy of regulation aiming at the citizen as a customer.